Role of Titanium Dioxide Nanoparticles in Forensic Science - Parthasarathy K.P.; Arkapravo Dey; Kajol Bhati; Rajeev Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
The use of science in the criminal justice system is known as forensic science. Justice is upheld through a proper analysis and assessment of the evidence. Due to factors like𿿿re, explosion, environmental changes, water, dirt, and any thers, crime scenes are usually damaged. The most reliable method of identifying a person is by their𿿿ngerprints, which is also one of the evidence types that are mst frequently found at crime scenes. The perpetrator frequently makes a concerted effort to destroy a𿿿ngerprint that contains crucial evidence. Due to their extreme ssitivity, nanoparticles are used to improve latent𿿿ngerprints on porous, semiporous, and nonporous surfaces. The problem wit the traditional 𿿿ngerprint development technique is that it is not that durable for a longer period of time. The particle size of the black powder and the other nano traditional powders are much more as compared to the size of the particles. In addition to adhesives, titanium dioxide (TiO2 ), a common paint pigment, can be suspended in a surfactant and utilized as a powder suspension to remove latent impressions from a variety of surfaces. It is a tiny, non-Áammable, non-toxic powder that is white in colo and smaer than one micron in diameter. AÁatoxin genes can be identi𿿿ed usin forsic genetics by adding silver and titanium dioxide nanoparticles to real-time PCR. It can also be used to detect explosives. Similarly, there are other applications as well. Therefore, this review paper will discuss the use of titanium dioxide nanoparticles in forensic research.